Income misperception and populism - Thilo N. H. Albers; Felix Kersting; Fabian Kosse (University of Würzburg, Department of Economics, 2023)
We propose that false beliefs about own current economic status are an important factor for explaining populist attitudes. Eliciting subjects' receptiveness to rightwing populism and their perceived relative income positions in a representative survey of German households, we find that people with pessimistic beliefs about their income position are more attuned to populist statements. Key to understanding the misperception-populism relationship are strong gender differences in the mechanism: men are much more likely to channel their discontent into affection for populist ideas. A simple information provision does neither sustainably reduce misperception nor curb populism.
urn:nbn:de:bvb:20-opus-321696
Keywords: D63; D72; D91; P16; 330; Perception; Income; Populism